MWCNTs/ZnO Nanofibers Fabrication, Properties and Applications - Badry, Magda Dawy (JOURNAL OF ADVANCES IN PHYSICS, 2019)
Electrospun MWCNTs nanofibers (CNF1, CNF2 and CNF3) with different concentrations of MWCNTs (0.3, 1.5, 2 wt%), respectively, were deposited on Aluminum foil substrates. Also,Zinc AcetatedihydrateZn(CH3COO)2.2H2O (ZNF) and MWCNTs/zinc acetate (CZNF)nanofiberswere deposited on Aluminum foil substratesand annealed in the presence of oxygen at 400 oC. The resultant fibers were characterized using X-ray differaction (XRD), scanning electron microscope with energy dispersive X-Ray spectrophotometry (SEM,EDX), Fourier transform infrared (FTIR). SEM,EDX and FTIR exhibited a total decomposition of the organic precursor after calcination and formation of zinc oxide (ZONF and CZONF). The mean fiber diameter was found to be increased with increasing MWCNTs concentration and ranged 490-767 nm. XRD patterns indicated that ZnO was corundum with the hexagonal wurtzite structure. The crystallite size of ZONF and CZONF were determined by shurrer equation to be26 and 29.7 nm, respectively. The optical analysis indicated that the percentage transmittance increased after calcination.The band gap for the electrospun fibers before and after calcination was calculated. CZONF nanofibers have electrical properties similar to those of semiconductors. The testedcompounds CNF2, CNF3, CZNF and CZONF exhibited different activities against the bacteriaand yeast pathogen Candidaalbicans. CZNF compound is the most active against the bacteria and yeast pathogen. So, these compounds can be used as food packaging.